Lagrangian Mechanics in Rotating Mechanical Systems - Saúl Hernández Moreno, Maickol Eduardo Rachen, Gonzalo Moreno (International Journal of Advanced Science and Technology, 2020)
This article is the product of the research “Mechanics Lagragian is rotating mechanical systems”, developed at the Faculty of Mechanical Engineering of the University Santo Tomas during the year 2019.Today, the aerospace industry employs more and more rotating mechanical systems in the preparation of astronauts for the stellar voyage, employing robots and programmed components, this article presents a Lagrangian analysis for the solution of these problems.The aim is to obtain differential equations of motion that were used with the method of the Lagrange equations from the relation of the constraint equations in position, constraint equations in velocity, non-conservative loads and the kinetic and potential energies of the mechanical system Under analysis, it allows us to solve dynamic problems applied to the aerospace industry.Keywords: Research, Mechanism, Movement, Lagrange, Aerospace, Centrifuge.